Fatores que caracterizam a adoção do Business Process Management (BPM) pelas organizações - Soso, Francis André (Universidade do Vale do Rio dos Sinos, 2016)
The adoption of Business Process Management (BPM) is an issue of interest organizations and also of research in Management and Information Technology (IT) for its potential to improve organizational performance. However, the factors which characterize its adoption are not clear in the literature because the existing research present limitations related to the context, participating public, scope of concepts and market sector where they were performed. Therefore the aim of this study was to analyze which factors characterize the adoption of BPM in organizations. For this purpose was identified in the literature the factors that characterize this adoption and the critical success factors (CSF) relating them with ten principles proposed by Brocke et al. (2014a). From then it developed and validated an instrument to measure the implementation and use of BPM concepts in organizations. Finally we analyzed the organizational practices associated with this adoption. The method used to achieve these goals was the survey type applied in a professional public related to the subject of research in the period from 08/28/2015 to 11/16/2015. The sample reached 352 respondents and data collection occurred by questionnaire distributed over the Internet. For data analysis was used as a technical exploratory analysis and structural equation modeling (SEM) and as a method confirmatory factor analysis (CFA). After adjustments to the model analysis results indicated the validity and reliability of research instrument. Finally, bring forward the contribution of this research to indicate the ten factors that characterize the adoption of BPM by organizations. These are: internal characteristics, process modeling, synergy between departments, clearly at the strategic level, commitment, roles and responsibilities, value chain, prioritization process, process culture and implementation.
Keywords: Business process management (BPM); Gestão de processo de negócio; Adoção de BPM; Fatores característicos; BPM adoption; Characteristic factors; ACCNPQ::Ciências Sociais Aplicadas::Administração